Gamma-Aminobutyric Acid Type A Receptor Genes and Their Related Epilepsies - Brafa Musicoro, Viviana; Sortino, Vincenzo; Pecora, Giulia; Tosto, Monica; Lo Bianco, Manuela; Soma, Rachele; Romano, Catia; Falsaperla, Raffaele; Praticò, Andrea D. (Journal of Pediatric Neurology, 2021)
Gamma-aminobutyric acid type A (GABA-A) receptor subunit gene mutations, which include GABRA1, GABRB3, GABRD, and GABRG2, are often involved in several genetic epilepsy syndromes and other neuropsychiatric diseases like autism spectrum disorder, schizophrenia, and anxiety. GABA-A are ligand-gated ionic channels, and are involved firstly in the fast inhibitory synaptic transmission of the central nervous system. The GABA receptors include the ionotropic GABA-A and GABA-C receptors and the metabotropic GABA-B receptors. According to the site in which mutations occur, they cause disorders in channel opening, “lock-and-pull” receptor system functioning, and capable of causing a specific epilepsy phenotype. The aim of this article is to summarize the most recent literature findings, considering genetic mutations, clinical features, genotype/phenotype correlation, and therapy about neurodevelopment diseases correlated to GABA receptors dysfunction, in particular epilepsy. According to our findings, we conclude that further mutation analysis could permit genotype–phenotype correlation and give more information about the best efficient treatment, even if—at present—more clinical and genetic studies are necessary.
Keywords: GABA receptor; metabotropic; ionotropic; epilepsies; encephalopathy